An Indigenous Method of Securing Ventriculoperitoneal Shunt Tube in Peritoneal Cavity - Kalra, Samir Kumar; Shah, Krishna; Tyagi, Sneyhil; John, Suviraj; Acharya, Rajesh (Indian Journal of Neurosurgery, 2021)
Introduction Ventriculoperitoneal shunt (VPS) is the most common procedure used for cerebrospinal fluid (CSF) diversion in hydrocephalus. Over the years, many technical, procedural, and instrument-related advancements have taken place which have reduced the associated complication rates. Shunt block is a very common complication irrespective of the shunt system used. The abdominal end of the shunt tube gets blocked usually due to plugging of omentum onto the shunt catheter. We describe a technique of catheter fixation and placement under vision coupled with omentopexy done laparoscopically to prevent this complication.Materials and Methods This technique was used in 23 patients (11 female, 12 male; range 16–73 years) afflicted with hydrocephalus from June 2016 and December 2019 after obtaining an informed consent, and the outcomes were noted in terms of shunt patency, complications, if any, and the need for revision.Results The median operation time was 90 minutes (range 35–160 minutes). All shunt catheters were still functional after a mean follow-up of 16.5 months (range 1–34 months) and none required revision.Conclusion Laparoscopic placement of shunt tube along with omental folding is a safe and effective technique for salvaging the abdominal end of VPS and may be helpful in reducing shunt blockage.
Keywords: Shunt block; ventriculoperitoneal shunt; laparoscopic VP shunt